Efficiency and Its Determinants: Firm-level Evidences from Micro Enterprises in Dibrugarh District of Assam. Issue 2 (June 2019) - Nomani, Rubab Fatema; Sen, Alok
This study estimates technical efficiency and examines its determinants in the micro-manufacturing enterprises in Dibrugarh, one of the most developed districts in the state of Assam in India. It is based on cross-sectional firm-level primary data, collected through a field survey from 115 micro-manufacturing enterprises in the district. The results of the data envelopment analysis suggests that the average technical efficiency score of the firms is quite low, which indicates a high degree of technical inefficiency in the production process. Further efficiency in the enterprises is more due to the inefficient conversion of inputs into outputs rather than due to scale inefficiency. An attempt has also been made to identify some firm-specific and entrepreneurial background variables responsible for inefficiency using the maximum likelihood Tobit regression model. The study reveals that skilled labour, firm-age, firm-size, experience of entrepreneur and gender of entrepreneur have a positive association with efficiency but the magnitude of influence is small. From a policy perspective, it is recommended that policies for rational downsizing of existing firms, along with their rehabilitation and reorganisation should be adopted to promote firm's efficiency performance. The empirical evidences also point to the need for industry-specific policy guidelines.